Repressor Element 1 Silencing Transcription Factor (REST) Governs Microglia-Like BV2 Cell Migration via Progranulin (PGRN). (25th November 2020) - Yu, Tongya; Lin, Yingying; Xu, Yuzhen; Dou, Yunxiao; Wang, Feihong; Quan, Hui; Zhao, Yanxin; Liu, Xueyuan
Abstract : Microglia activation contributes to Alzheimer's disease (AD) etiology, and microglia migration is a fundamental function during microglia activation. The repressor element-1 silencing transcription factor (REST), a powerful transcriptional factor, was found to play a neuroprotective role in AD. Despite its possible role in disease progression, little is known about whether REST participates in microglia migration. In this study, we aimed to explore the function of REST and its molecular basis during microglia migration under A β 1-42 -treated pathological conditions. When treated by A β 1-42 REST was upregulated through JAK2/STAT3 signal pathway in BV2 cells. And transwell coculture system was used to evaluate cell migration function of microglia-like BV2. Small interfering RNA (siRNA) targeting progranulin (PGRN) were delivered into BV2 cells, and results showed that PGRN functions to promote BV2 migration. REST expression was inhibited by sh-RNA, which induced BV2 cell migration obviously. On the contrary, REST was overexpressed by REST recombinant plasmid transfection, which repressed BV2 cell migration, indicating that REST may act as a repressor of cell migration. To more comprehensively examine the molecular basis, we analyzed the promoter sequence of PGRN and found that it has the potential binding site of REST. Moreover, knocking-down of REST can increase the expression of PGRN, which confirms the inhibiting effect of REST on PGRN expression. Further detection of double luciferase reporter gene also confirmed the inhibition of REST on the activity of PGRN promoter, indicating that REST may be an inhibitory transcription factor of PGRN which governs microglia-like BV2 cell migration. In conclusion, the present study demonstrates that transcription factor REST may act as a repressor of microglia migration through PGRN.